PENGELOLAAN HUTAN MANGROVE BERBASIS MASYARAKAT DI DESA KAMPUNG AMBONG KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - Natalia ., Kiolol; Wenny ., Tilaar; Wiske ., Rotinsulu (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze the socio-economic factors that affect the management of mangrove forests, as well as describe the management of community-based mangrove forests in Kampung Ambong Village, Likupang Timur District, North Minahasa District. This research was conducted for 3 (three) months from August to October 2017. The research used analytical descriptive approach using survey method. Sampling used purposive sampling method. Furthermore, participation analysis used Likert Scale. The survey was conducted to 55 respondents in Desa Kampung Ambong, Likupang Timur Sub-district, North Minahasa District. The results showed that based on the Rank Spearman correlation, socio-economic factors ie education level and membership in organization had enough influenced community participation in mangrove forest management. The participation rate of Kampung Ambong Village community in community-based mangrove forest management is categorized as 47.27%. Mangrove forest management have conducted by community members at Kampong Ambong Village, Likupang Timur Sub-district, North Minahasa District, in the form of rehabilitation which mostly plant Rhyzopora seedlings, as well as mangrove and supervision. This activity was carried out by the Tanjung Asa Forest Farmers Group.